Clinicopathologic Features and Risk Factors of Proteinuria in Transplant Glomerulopathy - Zhang, Qiang; Budde, Klemens; Schmidt, Danilo; Halleck, Fabian; Duerr, Michael; Naik, Marcel G.; Mayrdorfer, Manuel; Duettmann, Wiebke; Klauschen, Frederick; Rudolph, Birgit; Wu, Kaiyin (Frontiers in Medicine, 2021)
Background: Transplant glomerulopathy (TG) is one of the main causes of post-transplant proteinuria (PU). The features and possible risk factors for proteinuria in TG patients are uncertain. Methods:  We investigated all patients who had biopsy-proven TG from 2000 to 2018 in our center. The clinical and histological data were compared between two groups with or without PU (cut-off = 0.3 g/day). Spearman correlation analysis was used to evaluate the relationship between PU and pathological changes. The risk factors for PU in TG patients were determined by multivariable logistic regression analysis. Results: One hundred and twenty-five (75.76%) of all enrolled 165 TG patients had proteinuria ≥0.3g /day at the time of biopsy. TG patients’ PU level was significantly correlated with Banff lesion score cg (ρ = 0.247, P = 0.003), and mm (ρ = 0.257, P = 0.012). Systolic blood pressure ≥140 mmHg (OR 2.72, 95% CI 1.04-7.10, P = 0.041) , diastolic blood pressure ≥90 mmHg (OR 4.84, 95% CI 1.39-16.82, P = 0.013), peak PRA ≥5% (OR 6.47, 95% CI 1.67-25.01, P = 0.007), positive C4d staining (OR 4.55, 95% CI 1.29-16.11, 0.019), tacrolimus-based regimen (OR 3.5, 95% CI 1.28-9.54, P = 0.014), and calcium channel blocker usage (OR 4.38, 95% CI 1.59-12.09, P = 0.004) were independent risk factors for PU. Conclusions: Proteinuria is common in TG patients. systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥90 mmHg, peak PRA ≥5%, positive C4d staining, tacrolimus-based regimen, and calcium channel blocker usage are risk factors for proteinuria in TG patients.